Analisis Kelayakan Muatan PAI pada Film Animasi Nussa dan Rara serta Pemanfaatannya Sebagai Sumber Belajar di Sekolah Dasar - Ramadhani, Annisa; Khadijah, Siti; Ghofur, Abdul (Permata : Jurnal Pendidikan Agama Islam, 2024)
The rapid development of technology today makes educational institutions must improve to keep up with the times. Learning media must be made technology-based in accordance with current developments. Nussa and Rara Animation Film is an educational film based on Islamic religious education that is widely used in various Elementary Schools. The purpose of this study was to analyze the feasibility of PAI content in the animated film Nussa. This thesis also discusses the utilization of PAI content in Nussa and Rara animation as a learning resource in Elementary Schools. This research was designed with a qualitative research model, the instruments used in this research used observation sheets and transcription techniques. The episodes to be analyzed are "Eat Don't Just Eat, Good Is Easy, the Pillars of Islam and Hijaiyah Letters". The findings in this study indicate that of the four Nussa and Rara animated films, the episode of good is easy to obtain the feasibility of a very feasible category and the episode of hijaiyah letters obtained a partially feasible category. The utilization of Nussa and Rara animation media is used as a supporting source but has an important role in teaching and learning activities at school. The conclusion in this study answers the formulation of the problem that has been made at the beginning, so the title in this study is "Analysis of the Feasibility of PAI Content in Nussa and Rara Animated Film and its Utilization as a Learning Resource in Elementary School."Keyword : PAI Content; Nussa and Rara Animation; Learning Resources